Development of a novel phase change material emulsion for cooling systems - Shao, Jingjing; Darkwa, Jo; Kokogiannakis, Georgios (Elsevier, 2016)
In this paper, a novel phase change material emulsion (PCE-10) consisting of an organic PCM (RT10) and water has been developed. Its thermophysical properties such as heat of fusion, viscosity and sub-cooling temperature have been established. The chemical stability during both storage and discharge periods have also been evaluated. The results indicate low sub-cooling temperature and relatively long period of stability without any sign of segregation but the viscosity was found to be much higher than that of water.